MANET Expansion Security Challenges Attacks and Intriguing future Trends - Agarwal, Swati; Kaur, Rupinder; Agarwal, Tushar (International Journal of Computer Sciences and Engineering, 2025)
In recent years, the interest in wireless networks has grown up because of the provision of wireless communication devices. While planning an ad hoc network specifically, we are worried about the abilities and confinements that the physical layer forces on the network performance. While designing MANET one can keep in mind, the types of difficulties we face, including signal security, the reliability of Portable devices and dynamic nature of nodes. Specialist brings up that the MANET, now a state of business investigates, was at first used as a piece of military endeavours, joining into vital frameworks and Defence Advanced Research Projects Agency (DARPA) wanders. In this paper we have depicted the advancement and essential issues of wireless ad-hoc network system and in addition we have also discussed vulnerabilities of MANET and Security services it has. This paper also highlights some intriguing future application of the MANET. At last we have proposed that how one can make MANET more powerful by the use of SMART DUST Technology.